The transverse myocutaneous gracilis flap (TMG) for breast reconstruction: ipsi vs. contralateral harvest: aesthetic outcome and refinement procedures - Vollbach, Felix Hubertus; Neuss, Clara; Siegwart, Laura C.; Bigdeli, Amir Khosrow; Kneser, Ulrich; Fansa, Hisham; Kotsougiani-Fischer, Dimitra (Breast cancer, 2023)
The TMG flap is a popular choice for breast reconstruction. However, it remains unclear whether the side of flap harvest, subsequent flap shaping and inset impacts breast appearance and volume dispersion. This study compares the aesthetic outcome of the reconstructed breast following TMG flap harvest from the ipsilateral or contralateral thigh.
Online veröffentlicht: 1. Juli 2023
Gesehen am 07.08.2024